(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: To improve the nutritional value of straw, which is available in large quantities as a byproduct of grain cultivation, the fermented juice of epiphytic lactic acid bacteria was used to enhance the fermentation of wheat straw silage, stimulate lactic acid production and improve Nutritional value of hay through anaerobic fermentation during silage. Materials and Methods: The fermented juice was prepared from wild reed with three sources of soluble carbohydrates and two levels for each source including glucose at level (1 and 2%, w/v) (A, B), cane molasses at (3 and 5%, w/v) (C, D) and date molasses at( 3 and 5%, w/v) (E, F) . According to this, Six samples of wheat straw silage prepared by adding fermented juice at a level of 1%. While distilled water was added in an amount similar to the amount of fermented juice when making the control group (G). Results: Results showed that addition fermented juice of epiphytic lactic acid bacteria improved (P<0.01) the Dry matter content of silage samples, and improved fermentation characteristics, increase (P<0.01) was observed in the concentration of lactic acid and volatile fatty acids. Moreover, lower (P<0.01) Dry Matter losses were estimated in wheat straw silage prepared with addition of fermented juice. Conclusions: Addition fermented juice of lactic acid bacteria, regardless of the source and the level of soluble carbohydrates added to it, improved the fermentation quality of wheat straw silage, aerobic stability and dry matter loss.